Attitudes and concerns regarding booster dose of COVID-19 vaccine among Egyptian patients with autoimmune and rheumatic diseases: a cross-sectional survey study - Samar Tharwat; Elshimaa Saad Eleraky; Toqa Adel; Mohammed Kamal Nassar; Marwa Saleh (Taylor & Francis Group, 2023)
Abstract Background COVID-19 booster dose vaccination acceptance and actual vaccination behavior is not known among Egyptian individuals with autoimmune and rheumatic diseases (ARDs). The aim of this study was to investigate the acceptability of booster dose of the COVID-19 vaccine, as well as the factors that drive and inhibit that acceptance among Egyptian patients diagnosed with ARDs. Methods This interview-based, cross-sectional analytical study was carried out on ARD patients from 20 July to 20 November 2022. A questionnaire was created to assess sociodemographic and clinical data, as well as COVID-19 vaccination status and the intention to receive a COVID-19 vaccine booster dose, perception of health benefits of it in addition to the perceived barriers and/or concerns. Results A total of 248 ARD patients were included, with a mean age of 39.8 years (SD = 13.2), and 92.3% were females. Among them, 53.6% were resistant to the COVID-19 booster dose, whereas 31.9% were acceptant and 14.5% were hesitant. Those who were administering corticosteroids and hydroxychloroquine shown significantly greater booster hesitancy and resistance (p = 0.010 and 0.004, respectively). The primary motivation for taking a booster dose among the acceptant group was own volition (92%). Most acceptants believed that booster dose can prevent serious infection (98.7%) and community spread (96.2%). Among the hesitant and resistant groups, the main concerns for booster dose were fear about its major adverse effects (57.4%) and long-term impact (45.6%). Conclusions There is a low acceptability rate of booster dose of COVID-19 vaccine among Egyptian patients with ARD diseases. Public health workers and policymakers need to make sure that all ARD patients get clear messages about accepting the COVID-19 booster dose.